Postoperative Evaluation of the Quality of Life, Depression, and Anxiety of Temporal Lobe Epilepsy Cohort: A Single Institute Experience in Indonesia - Bakhtiar, Yuriz; Pratama Brilliantika, Surya; Bunyamin, Jacob; Arifin, Muhammad Thohar; Hardian, Hardian; Bintoro, Aris Catur; Muttaqin, Zainal (Frontiers in Neurology, 2021)
Background: Besides seizure control, quality of life (QoL) should be considered as an equally important outcome for epilepsy surgery service providers. The paucity of QoL reports from developing countries has enlarged the representation gap between rich and less resourceful countries. In this study, we evaluated postoperative QoL in the Indonesian drug-resistant epilepsy cohort where the epilepsy surgery service faces limited resources availability. Methods: We evaluated the QoL in patients with temporal lobe epilepsy who underwent surgery in our epilepsy surgery center in Semarang, Indonesia, from 2001 until 2015. The follow–up period started in 2018 through 2019. Postoperative QoL, depression, and anxiety were evaluated with self-reporting questionnaires including the Quality of Life in Epilepsy Inventory-31, Beck Depression Inventory-II, and Zung Self-Rating Anxiety Scales. Results: Forty returned questionnaires were included in the analysis (male 25, 62.5%; mean age 27.6±9.05 years). The seizure-free cohort (n=22, 55.0%) reported higher scores in most QoL dimensions particularly adjustment, overall QoL, and seizure worry compared to those with persistent seizures. The overall QoL level was correlated with seizure freedom and seizure type. QoL dimensions were negatively correlated with anxiety and depression levels. Conclusions: Postoperative seizure freedom was a major factor of postoperative QoL level. Besides seizure freedom, anxiety and depression levels were also negatively correlated with QoL levels in the Indonesian population.